Central Nervous System Cryptococcosis in Patients With Sarcoidosis: Comparison With Non-sarcoidosis Patients and Review of Potential Pathophysiological Mechanisms - Prevel, Renaud; Guillotin, Vivien; Imbert, Sébastien; Blanco, Patrick; Delhaes, Laurence; Duffau, Pierre (Frontiers in Medicine, 2022)
Introduction: Cryptococcus neoformans infection of central nervous system (CINS) is a devastating opportunistic infection, historically described in acquired-immunodeficiency syndrome (AIDS) patients, but also described with sarcoidosis; the impairment of cell-mediated immunity and long-term corticosteroid therapy being evoked to explain this association. Nevertheless, this assertion is debated and the underlying pathophysiological mechanisms are still unknown. The aims of this study were (i) to describe the clinical and biological presentation, treatments and outcomes of CINS patients with and without sarcoidosis, (ii) to review the pathophysiological evidence underlying this clinical association. Patients and Methods: every patient with positive cerebrospinal fluid (CSF) cryptococcal antigen testing, India ink preparation and/or culture were included and patients. Quantitative variables are presented as mean ± standard deviation and compared by use of the Mann-Whitney Wilcoxon rank-sum test. Categorical variables are expressed as number of patients (percentage) and compared by use of the χ2 or Fisher tests. Results: During the study period, 16 patients experienced CINS, 5 of them (31%) associated with sarcoidosis. CINS symptoms, biological and CSF features were similar between CINS patients with and without sarcoidosis except regarding CD4 cells percentages and CD4/CD8 ratio which were higher in those with sarcoidosis (respectively 47 ±12 vs 22 ±18, p: 0.02 and 2.24 ±1.42 vs 0.83 ±1.10, p: 0.03). CINS patients with and without sarcoidosis received similar treatments but those with sarcoidosis received it for a shorter duration. CD4 cell levels do not seem to explain the association between sarcoidosis and cryptococcosis. B-1 cell deficiency or lack of IgM could be part of the explanation. The presence of anti-GM-CSF antibodies in a subset of patients with sarcoidosis could impair macrophage phagocytic function and so explain this increased susceptibility to cryptococcosis. Conclusion: Sarcoidosis seems to be frequently associated with CINS. CINS diagnosis should be considered in the case of a patient affected by sarcoidosis with central neurological symptoms regardless of obvious immunosuppression or long-term corticosteroids intake. Various pathophysiological mechanisms could be involved in this predisposition, especially a defect in macrophage phagocytosis. Further studies are strongly needed to better understand the mechanisms underlying this association and to better identify at-risk patients.